2003
DOI: 10.1093/jhered/esg090
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of QTL for Body Conformation and Behavior in Cattle

Abstract: Genome scans for quantitative trait loci (QTL) in farm animals have concentrated on primary production and health traits, and information on QTL for other important traits is rare. We performed a whole genome scan in a granddaughter design to detect QTL affecting body conformation and behavior in dairy cattle. The analysis included 16 paternal half-sib families of the Holstein breed with 872 sons and 264 genetic markers. The markers were distributed across all 29 autosomes and the pseudoautosomal region of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 37 publications
6
77
3
1
Order By: Relevance
“…In spite of these findings, the study could not verify a QTL for flight distance at the distal end of BTA29 in a Holstein 3 Charolais population (Gutié rrez-Gil et al, 2008). The putative QTL near BMS764 (14.1 cM) found for German Angus confirms earlier results of a QTL in Holstein cattle (Hiendleder et al, 2003). Therefore, this region seems to play an important role in different patterns of behaviour and across breeds and should be analysed in more detail.…”
Section: Introductioncontrasting
confidence: 63%
See 2 more Smart Citations
“…In spite of these findings, the study could not verify a QTL for flight distance at the distal end of BTA29 in a Holstein 3 Charolais population (Gutié rrez-Gil et al, 2008). The putative QTL near BMS764 (14.1 cM) found for German Angus confirms earlier results of a QTL in Holstein cattle (Hiendleder et al, 2003). Therefore, this region seems to play an important role in different patterns of behaviour and across breeds and should be analysed in more detail.…”
Section: Introductioncontrasting
confidence: 63%
“…A quantitative trait locus (QTL) for behaviour during milking in Holstein-Friesian cows was identified in a whole genome scan at BMS764 at BTA29 (Hiendleder et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Schrooten et al (2000) found no QTL correlated with temperament during milking in Holstein-Friesian cattle, but three genomic regions with suggestive linkage for milking speed where located on chromosomes 2, 3 and 23. In contrast, Hiendleder et al (2003) detected four QTL for behaviour during milking on the chromosomes 5, 18, and 29 in the same breed. Additionally, these QTL were in close proximity to the QTL identified for milking speed in the same study, indicating that these might be single QTL affecting both traits.…”
Section: Genomic Regions Associated With Temperament Traitsmentioning
confidence: 80%
“…Therefore behaviour is commonly evaluated during routine handling processes since they are not highly time and space consuming. In dairy cattle, for example, behavioural assessment is usually conducted by scoring temperament for nervousness, aggressiveness or docility during milking by farmers or milking technicians (Dickson et al, 1970;Hiendleder et al, 2003). However, in beef cattle, scoring during weighing is a frequent test for determining temperament.…”
Section: Measuring the Behavioural Phenotype In Cattlementioning
confidence: 99%